The need for a new model of the physician–patient relationship: a challenge for modern medical practice - Aoun, Antoine; Al Hayek, Sibelle; El Jabbour, Flora (Family Medicine & Primary Care Review, 2018)
A revolution in the field of medicine, enhancing knowledge and techniques, has been affecting, for the last fifty years, all aspects of healthcare, bioethics and finance. It is in this new context that we should relocate the physician–patient relationship and identify the different form that it is currently taking. The aim of this review paper is to evaluate the different models of the physician– –patient relationship, described in medical literature, and to emphasize the need for an innovative interaction that fits the new dimensions of modern medical practice. During the last decade, the debate has grown around the opposition between several patterns of the physician–patient relationship. The model of mutual participation of Szasz and Hollender (involving a relationship set between equals and built on helpfulness) and the deliberative model of Emanuel and Emanuel (encouraging the patient’s independence in decisionmaking, which occurs after the physician’s helpful advice) were considered appropriate models of the physician–patient relationship, with several limitations. In modern medi.cine, patients have an increasing number of needs that have to be satisfied: personal and familial, psychological and social, material and spiritual. The physician is rarely adequately prepared for the new needs and the new dimensions of the current physician–patient interaction.